Cancer associated thrombosis and mortality in patients with cancer stratified by khorana score risk levels. (20th September 2020) - Khorana, Alok A.; Kuderer, Nicole M.; McCrae, Keith; Milentijevic, Dejan; Germain, Guillaume; Laliberté, François; MacKnight, Sean D.; Lefebvre, Patrick; Lyman, Gary H.; Streiff, Michael B.
Abstract: Background: The Khorana score (KS) clinical algorithm is used to predict VTE risk in cancer patients. The study objective was to evaluate VTE and survival rates among patients newly diagnosed with cancer and stratified by KS in a real‐world population. Methods: Data from the Optum ® Clinformatics ® DataMart database between 01/01/2012–09/30/2017 was used to identify adults with ≥ 1 hospitalization or ≥ 2 outpatient claims with a cancer diagnosis (index date). Only patients who were initiated on chemotherapy or radiation therapy were included. Patients were classified based on KS (KS = 0, 1, 2 or ≥ 3). Time‐to‐first VTE and survival were evaluated from the index date to the earliest among end of data availability or insurance coverage, death, or 12 months post‐index using Kaplan‐Meier (KM) analyses. Results: A total of 2, 488 (KS = 0); 2, 125 (KS = 1), 1, 074 (KS = 2), and 507 (KS ≥ 3) cancer patients were included. The 12‐month KM rates of VTE were 3.1%, 5.4%, 7.9%, and 14.9% (associated median time to VTE of 2.7, 3.0, 1.4, and 1.7 months) among KS = 0, 1, 2, and ≥ 3 cohorts, respectively. Corresponding adjusted hazard ratios (95% CIs) relative to the KS = 0 cohort were 1.72 (1.25‐2.38), 2.46 (1.73‐3.50), and 4.99 (3.40‐7.31) for the KS = 1, 2, and ≥ 3 cohorts, respectively (all P  < .001). Regardless of KS, patients with VTE had significantly lower survival rates than those without. Conclusions: This real‐world claims‐based cohort study of newly diagnosed cancer patients showed significantly higher rates of VTE with increased KS, confirming its predictive ability. Moreover, VTE was associated with lower survival rates within each KS cohort. Abstract : This cohort study evaluated the risk of VTE and survival rates among patients newly diagnosed with cancer and stratified by Khorana score (KS) in a real‐world population. The present findings indicate that the rates of VTE significantly increased with KS, confirming its predictive ability. Moreover, VTE was associated with lower survival rates within each KS cohort.